Contribution of Adrenaline to the Fibrinolytic Activity Evoked by E. Coli Endotoxin in the Rat - Fracasso, J F; Rothschild, A M (Thrombosis and Haemostasis, 1983)
Intravenous injection of E. coli endotoxin (ETX), of adrenaline (AD) or of carbamylcholine (CBCH), caused fibrinolytic activity (FA), directly detectable on plasminogen-rich fibrin plates, to appear in the plasma of the rat. Adrenodemedul- lation abolished responses to ETX or CBCH, but enhanced those to AD. Rats given ETX exhibited marked hypotension, followed by a compensatory phase of normotension abolished by adrenodemedullation and significantly attenuated by phenoxy- benzamine, an a-adrenergic blocking agent which however failed to block FA caused by either ETX or AD. Aspirin, but not indomethacin, inhibited FA evoked by ETX, AD or CBCH. These results suggest that FA evoked by ETX in the rat is caused by AD released from the adrenal gland and does involve the fatty acid cyclooxygenase system.
Keywords: Fibrinolysis; Endotoxin; Adrenaline; Aspirin